Treatment outcomes of mucosal melanoma of head and neck: Efficacy of immune checkpoint inhibitors for advanced disease - Ohshima, Shusuke; Ueki, Yushi; Yokoyama, Yusuke; Takahashi, Takeshi; Shodo, Ryusuke; Yamazaki, Keisuke; Okabe, Ryuichi; Matsuyama, Hiroshi; Togashi, Takafumi; Takatsuka, Sumiko; Takenouchi, Tatsuya; Horii, Arata (Frontiers in Surgery, 2022)
Background: Head and neck mucosal melanoma (HNMM) is a rare and aggressive subtype of melanoma. HNMM often develops as a recurrent or metastatic disease, and its prognosis is worse than that of cutaneous melanoma. Recent large-scale clinical studies have reported favorable outcomes with immune checkpoint inhibitors (ICIs) for melanoma. However, these clinical trials included only a small number of HNMM cases. This study aimed to estimate treatment outcomes and prognostic predictors of ICIs for advanced HNMM. Methods: Cases of advanced HNMM, defined as unresectable or metastatic HNMM at the initial diagnosis (five patients) or development of recurrent/metastatic HNMM after initial treatment (27 patients), were included in this study. Survival analysis and a search for prognostic factors were performed for these 32 patients. Furthermore, the detailed clinical course of patients who received ICI treatment was investigated. Results: The median overall survival (OS) of 32 patients with advanced HNMM was 25.3 months. The estimated 1-, 3-, and 5-year OS rates were 68.4%, 42.8%, and 34.3%, respectively. Fourteen patients (43.7%) received ICIs, whereas 18 (56.3%) did not. Univariate analysis showed that ICI treatment was the only factor associated with a better 1-year OS. Patients who received ICI treatment had significantly longer OS (median OS: not reached, 1-year OS: 85.7%) than those who did not (median OS: 11.3 months, 1-year OS: 54.5%). The overall response and disease control rates of patients who received ICI treatment were 50% and 64.3%, respectively. Patients who achieved complete response (CR) or partial response (PR) to ICI treatment survived significantly longer (1-year OS: 100%) than those who did not (1-year OS: 71.4%). Among the five patients who discontinued ICI treatment due to severe immune-related adverse events (irAEs), four did not receive salvage treatments but showed durable treatment effects and survived for 9.8-54.2 months at the end of the follow-up period. Conclusions: ICI treatment achieved a favorable OS for advanced HNMM. CR/PR to ICI treatment and discontinuation owing to severe irAEs were favorable predictors of OS.